STRUCTURILE NATO AMPLASATE PE TERITORIUL ROMÂNIEI - Andrei, Narcis (Revista de Știinţe Politice şi Relaţii Internaţionale)
Romania was in a state of insecurity following the conclusion of the Cold War, when the Soviet Union collapsed and the communist governments in Europe fell. As a result, it was necessary for Romania to adjust to the changing geopolitical conditions, which made joining NATO easier. The 14-year process of accession, which involved several visits between Romanian and Western officials, was not simple. In 2004, the procedure came to a successful conclusion. The establishment of military institutions in reaction to geopolitical events along the Romanian border helped Romania grow into a significant state in the area throughout time. NATO has remained close to its members over the years, serving as a collective security guarantee. The military formations, some of which serve as training grounds for intelligence professionals, are responsible for ensuring the optimal coordination of the Alliance’s forces in the Southeast region of Europe. Within this Alliance, Romanians have succeeded in holding important roles.